2010
DOI: 10.1093/carcin/bgq012
|View full text |Cite
|
Sign up to set email alerts
|

Selection of cancer cells with repressed mitochondria triggers colon cancer progression

Abstract: The contribution that mitochondrial bioenergetics could have in cancer development is debated. Here, we have generated HCT116-derived colocarcinoma cell lines expressing different levels of the beta catalytic subunit of the mitochondrial H+-adenosine triphosphate synthase to assess the contribution of mitochondrial bioenergetics in colon cancer progression. The generated cells exhibit large ultrastructural, transcriptomic, proteomic and functional differences in their mitochondria and in their in vivo tumor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
129
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 45 publications
16
129
1
Order By: Relevance
“…Remarkably, oligomycin treatment of IF1-silenced cells restored the original rates of aerobic glycolysis (Fig. 4A), strongly supporting the link between the bioenergetic activity of mitochondria and glucose consumption rates (12,15). Consistently, the determination of the activity of oxidative phosphorylation indicated that IF1-silenced cells had a higher oligomycin sensitive respiratory rate than controls (Fig.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Remarkably, oligomycin treatment of IF1-silenced cells restored the original rates of aerobic glycolysis (Fig. 4A), strongly supporting the link between the bioenergetic activity of mitochondria and glucose consumption rates (12,15). Consistently, the determination of the activity of oxidative phosphorylation indicated that IF1-silenced cells had a higher oligomycin sensitive respiratory rate than controls (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Glycolysis is known to provide an advantageous phenotype that favors cellular proliferation and invasion (15,37). Moreover, limiting the activity of the H ϩ -ATP synthase also contributes to tumor growth because oxidative phosphorylation is required for the efficient execution of cell death (38 -40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 In addition to rRNA and tRNA genes, the phylogenetically conserved region of mitochondrial DNA includes sequences encoding for some of the polypeptides which have a role in the control of electron chain transport, such as cytochrome oxidase I and II subunits (MT-CO1/MT-CO2). Mutations affecting these genes have been identified in colorectal cancer cell lines as well as in tumor specimens from colorectal cancer patients.…”
mentioning
confidence: 99%